NPK Fertilizer Dosage Treatment On the Growth and Yield of Red Spinach (Amaranthus Tricolor L.) - Nurul Huda; Sri Hidayati (Agricultural Science, 2022)
The purpose of this study was to determine the extent of the effect of the use of fertilizer doses NPK compound on the growth and yield of red spinach (Amaranthus tricolor L.), This research method used a Randomized Block Design (RAK) consisting of six (6) treatments with three (3) replications and two (2) sample plants. The treatment was given, namely the dose of NPK Compound Fertilizer which consisted of six (6) doses, A = No NPK Compound Fertilizer (Control), B = NPK Compound Fertilizer 100 kg/Ha (0.05 gr/tan = 0.5 gr/ 10 tons/polybag), C = NPK Compound Fertilizer 200 kg/Ha (0.10 gr/tan = 1.0 gr/10 tons/polybag), D = NPK Compound Fertilizer 300 kg/Ha (0.15 gr/tan = 1.5 gr/10 tons/polybag), E = NPK Compound Fertilizer 400 kg/Ha (0.20 gr/tan = 2.0 gr/10 tons/polybag) and F = NPK Compound Fertilizer 500 kg/Ha ( 0.25 gr/tan = 2.5 gr/10 tons/polybag), for analysis and assisted by using Excel. Research Results There was a significant effect on the observed variables of plant height, number of leaves and wet weight of red spinach plants due to the treatment of using various doses of NPK compound fertilizers and effective (appropriate) doses or optimum doses of NPK compound fertilizers during growth and yield of red spinach plants. The dose of NPK compound fertilizer treatment was 300 kg/Ha (0.15 gram/plant), while the maximum dose was indicated by the treatment dose of NPK compound fertilizer 500 kg/Ha (0.25 gram/plant), because statistically both treatments of compound fertilizer dose The NPK was not significantly different.